Assessment of Extramammary Paget Disease by Two-Photon Microscopy - Hristu, Radu; Eftimie, Lucian G.; Stanciu, Stefan G.; Glogojeanu, Remus R.; Gheorghita, Pavel; Stanciu, George A. (Frontiers in Medicine, 2022)
Two-photon microscopy techniques are nonlinear optical imaging methods which are gaining momentum in the investigation of fixed tissue sections, fresh tissue or even for in vivo experiments. Two-photon excited fluorescence and second harmonic generation are two nonlinear optical contrast mechanisms which can be simultaneously used for offering complementary information on the tissue architecture. While the former can originate from endogenous autofluorescence sources (e.g., NADH, FAD, elastin, keratin, lipofuscins, or melatonin), or exogenous eosin, the latter is generated in fibrillar structures within living organisms (e.g., collagen and myosin). Here we test the ability of both these contrast mechanisms to highlight features of the extramammary Paget disease on fixed tissue sections prepared for standard histological examination using immunohistochemical markers and hematoxylin and eosin staining. We also demonstrate the label-free abilities of both imaging techniques to highlight histological features on unstained fixed tissue sections. The study demonstrated that two-photon microscopy can detect specific cellular features of the extramammary Paget disease in good correlation with histopathological results.